Biogeographical survey of indigenous yeasts from the vineyards of the Azores Archipelago - Neves, J. Drumonde (2010)
This study aims at the characterization of the fermentative yeasts flora of the vineyards of the Azores islands, for biodiversity preservation and the constitution of a Saccharomyces cerevisiae strain collection as a genetic resource for future strain selection and improvement. During the harvest of 2009, 88 grape samples were collected from eight islands of the archipelago that belonged to traditional (Arinto, Verdelho and Terrantez) and hybrid (“American”) grape varieties. The sampling plan covered 36 locations, including vineyards in appellations of origin and vineyards that were abandoned for more than 5 years. Forty nine spontaneous fermentations were achieved from the musts of 88 grape samples. About 83% of the musts obtained from grapes of traditional varieties finished fermentation, while this value was 47% and 33% for musts from hybrid varieties in non-abandoned and abandoned vineyards, respectively. From the final phase of each fermentation, 30 isolates were obtained, resulting in a total of 1470 isolates. The molecular identification was performed by restriction fragment length polymorphism analysis (RFLP) of ITS sequences. The S. cerevisiae strains were differentiated by the comparison of polymorphic patterns that were obtained from interdelta sequences amplification. Six hundred and sixty isolates of non-Saccharomyces species and 810 isolates of S. cerevisiae were obtained, which were classified in 168 strains. Surprisingly, the percentage of S. cerevisiae in fermentations performed with grapes from abandoned vineyards was significantly higher (75%) compared to the values determined for non-abandoned vineyards (56%, for both traditional and hybrid varieties). Contrarily, the number of S. cerevisiae strains per fermentation was lower (3-11 strains) in samples collected from abandoned vineyards compared to non-abandoned vineyards (1-23 strains). The relative proportion of S. cerevisiae and non-Saccharomyces species was not associeated with the grape variety, but rather the type of vineyard. The highest number of S. cerevisiae strains per fermentation was observed in samples collected from the Graciosa Island. Our results show that the vineyards on the Azores Islands have a high genetic diversity of S. cerevsiae, whereas this species can also be found in vineyards with no human intervention.